Magma origins and geodynamic implications for the Makran-Chagai arc from geochronology and geochemistry of Bazman volcano, southeastern Iran - Ghalamghash, Jalil; Schmitt, Axel Karl (Journal of Asian earth sciences, 2019)
Bazman is an isolated voluminous (3497m elevation; >300km2) composite volcano that is located within the western segment of the Makran-Chagai arc. This arc obliquely tracks the modern EW-trending trench offshore the Oman sea coast of Iran and Pakistan, with several Quaternary stratovolcanoes (Bazman and Taftan in SE Iran, and Kuh-i-Sultan in western Pakistan) superimposed on a preexisting Neogene arc. High spatial resolution and high sensitivity U-Pb geochronology using Secondary Ionization Mass Spectrometry (SIMS) yielded four clusters of zircon ages for Bazman volcanic rocks which range from ca. 8.6Ma to 41ka. Lava and pyroclastic materials erupted between 8.6 and 5.9Ma forming a thick Neogene volcanic succession (Ngv). These deposits were intruded by hypabyssal andesite-dacite domes at ca. 4.1Ma. The next younger group of the Quaternary Bazman center comprises several eruptive pulses at 1.37Ma, 1.13Ma, 0.943Ma, 0.853Ma and 0.635Ma, which constructed the main edifice around a central vent through alternating eruptions of lava and pyroclastic rocks (Qtv and Qa2). Subsequently, ignimbrite flows also sourced from the main vent erupted at 0.59 and 0.47Ma, and covered the earlier erupted deposits. The youngest dated eruptive phase (Qa3) comprises the emplacement of dacitic to andesitic lava around the top of volcano. Based on Uranium-series (238U-230Th) disequilibrium in Qa3 zircons, model ages of ca. 41ka define a maximum eruption age of these lavas, which tapped a long-lived magma reservoir with zircon crystallization ages predating eruption by 10’s to 100’s of ka. Low- medium-K calc-alkaline basaltic-andesitic eruptions formed parasitic cones located on northeastern flanks of the edifice as the youngest unit (Qa4) of Bazman. Both Neogene and Quaternary rocks from Bazman volcano exhibit homogeneous trace element characteristics, including enrichments in large ion lithophile elements (LILE) and light rare earth elements (LREE) relative to the high field strength elements (HFSE) and heavy rare earth elements (HREE), respectively. High Th/Yb and negative anomalies of Ta, Nb and Ti are consistent with an enriched mantle source in a continental subduction zone. Trace element modeling for the most primitive basalts erupted at Bazman suggests an origin of parental magmas through ∼15% partial melting of an enriched spinell-lherzolite mantle, whereas the genesis of Bazman acidic volcanic rocks with SiO2>62% involves partial melting in the middle/lower continental crust which became subsequently overprinted through assimilation - fractional crystallization (AFC) processes. Compositional continuity of Quaternary Bazman volcanic rocks with their Neogene precursors implies a steady magma source above the subducted Oman slab. Consequently, subduction geometry in the Makran-Chagai arc has experienced little modification over the past few million years.